"There and Back Again": A Tale of a Discipline's Departure and Triumphant Return. (March 2023) - Norwood, James
Prevailing materialistic–determinist conceptions of extreme states (aka "psychosis") undermine the potential for authentic personal relationships essential to the healing process. The author demonstrates how psychedelic experiences have similar qualities to "psychotic" processes, insofar as they present opportunities to encounter and integrate disowned aspects of the self. Rather than being clearly determined by a "dysfunctional brain" or traumatic environment, extreme states are best understood through nonscientific epistemologies. Radically accepting communities are proposed as alternatives to treatment.